2014
DOI: 10.1103/physrevd.90.114025
|View full text |Cite
|
Sign up to set email alerts
|

Curvature of the chiral pseudocritical line in QCD

Abstract: We determine the curvature of the pseudocritical line of strong interactions by means of numerical simulations at imaginary chemical potentials. We consider Nf=2+1 stout improved staggered fermions with physical quark masses and the tree level Symanzik gauge action, and explore two different sets of lattice spacings, corresponding to temporal extensions Nt=6 and Nt=8. Both the renormalized chiral condensate and the renormalized chiral susceptibility are used to locate the transition. The determinations obtaine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
141
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 96 publications
(158 citation statements)
references
References 60 publications
17
141
0
Order By: Relevance
“…In the spirit of analytic continuation, this information could give hints for or against a critical point for real chemical potential. While our data don't show any influence of a possible endpoint nearby, it must be said that the Roberge-Weiss endpoint (which, in the setup with µ s = 0, lies at µ l,I /(πT ) ∼ 0.45 [7]) seems not to have any influence on these quantities either.…”
Section: The Continuum Limitmentioning
confidence: 75%
See 3 more Smart Citations
“…In the spirit of analytic continuation, this information could give hints for or against a critical point for real chemical potential. While our data don't show any influence of a possible endpoint nearby, it must be said that the Roberge-Weiss endpoint (which, in the setup with µ s = 0, lies at µ l,I /(πT ) ∼ 0.45 [7]) seems not to have any influence on these quantities either.…”
Section: The Continuum Limitmentioning
confidence: 75%
“…For finite size effects, we refer to the analysis already done in a previous study [7]. In that work, using data coming from N t = 6 lattices, we have shown that finite size effects are negligible on lattices having aspect ratio ≥ 4.…”
Section: Numerical Setupmentioning
confidence: 89%
See 2 more Smart Citations
“…[7][8][9]. In recent lattice studies [10,11] it has been shown that the potential gets modified and relevant consequences may arise at the level of heavy meson production and spectrum (see [12,13] and the references herein). In particular, at zero temperature the interaction becomes anisotropic due to the string tension σ which decreases in the direction parallel to the external field B, while it grows on the orthogonal plane; at larger T , in the confined regime below the pseudo-critical temperature T c , the external field is responsible of a precocious loss of the deconfining properties, in agreement with the picture of a decreasing T c due to the field itself.…”
Section: Introductionmentioning
confidence: 99%